Managing Migration from the Traditional to Modern Sector in Developing Countries - Karp, Larry (Washington, DC: World Bank, 2012)
This paper models the process of migration from a traditional to a modern sector. Migrants from the traditional sector experience a period of unemployment before finding modern sector jobs. Because of congestion in the process that matches the unemployed with jobs, an increase in the amount of unemployment increases the expected duration of unemployment for the representative migrant. Skilled workers can provide education and other services that decrease the expected duration of unemployment, but the competitive market under-provides these services. Congestion in the search process and the under-provision of migration services are market failures, requiring two types of government policies.